2014
DOI: 10.1093/carcin/bgu086
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine phenotype of gastric myofibroblasts and its loss with cancer progression

Abstract: Stromal cells influence cancer progression. Myofibroblasts are an important stromal cell type, which influence the tumour microenvironment by release of extracellular matrix (ECM) proteins, proteases, cytokines and chemokines. The mechanisms of secretion are poorly understood. Here, we describe the secretion of marker proteins in gastric cancer and control myofibroblasts in response to insulin-like growth factor (IGF) stimulation and, using functional genomic approaches, we identify proteins influencing the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…the growth factors, VEGFC and CTGF) and growth factor-associated proteins ( e.g. IGFBP3, -4, -5, -6), some of which have already been characterized in previous studies of myofibroblast secretomes ( 14 , 22 , 25 ). When flux is plotted against estimated k , this subset is readily distinguishable ( Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…the growth factors, VEGFC and CTGF) and growth factor-associated proteins ( e.g. IGFBP3, -4, -5, -6), some of which have already been characterized in previous studies of myofibroblast secretomes ( 14 , 22 , 25 ). When flux is plotted against estimated k , this subset is readily distinguishable ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Constitutively secreted proteins predominate in the secretomes of the two cells studied here. However, stromal myofibroblasts including CAMs may exhibit a modest regulated secretory pathway ( 22 ) and in this context it is interesting that a marker of the pathway, secretogranin-2 (SCG2), was identified and exhibited rapid label incorporation ( k = 0.274/h). Immunoblotting confirmed that secretion of SCG2 was stimulated by a short (30 min) stimulation with ionomycin, consistent with calcium-evoked exocytosis and the response was resistant to cycloheximide and BFA, consistent with release from storage vesicles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…; Balabanova et al. ). The present analysis therefore focused on a comparison of CCK2R expression in these two groups.…”
Section: Methodsmentioning
confidence: 96%
“…Microarray data on pairs of CAMs and corresponding ATMs from 13 gastric cancer patients have previously been deposited at http://www.ncbi.nlm.nih.gov/geo/query/ acc.cgi?acc=GSE44740. The TNM classification system (Sobin et al 2009) had been applied to these tumors which had shown that patients with early stage disease indicated by low lymph node involvement (pN0-1) had significantly longer survival than those with advanced disease indicated by high lymph node involvement (pN2-4) (51 vs. 12 months, respectively, P < 0.01) (Holmberg et al 2012;Balabanova et al 2014). The present analysis therefore focused on a comparison of CCK2R expression in these two groups.…”
Section: Microarray Datamentioning
confidence: 99%
“…Microarray 12 months, respectively, P < 0.01) (Holmberg et al 2012;Balabanova et al 2014). The present analysis therefore focused on a comparison of CCK2R expression in these two groups.…”
Section: Microarray Datamentioning
confidence: 93%